Novel mitochondrial complex I inhibitors restore glucose-handling abilities of high-fat fed mice. (April 2016) - Martin, Darren S D; Leonard, Siobhán; Devine, Robert; Redondo, Clara; Kinsella, Gemma K; Breen, Conor J; McEneaney, Victoria; Rooney, Mary F; Munsey, Tim S; Porter, Richard K; Sivaprasadarao, Asipu; Stephens, John C; et al.
Abstract : Metformin is the main drug of choice for treating type 2 diabetes, yet the therapeutic regimens and side effects of the compound are all undesirable and can lead to reduced compliance. The aim of this study was to elucidate the mechanism of action of two novel compounds which improved glucose handling and weight gain in mice on a high-fat diet. Wildtype C57Bl/6 male mice were fed on a high-fat diet and treated with novel, anti-diabetic compounds. Both compounds restored the glucose handling ability of these mice. At a cellular level, these compounds achieve this by inhibiting complex I activity in mitochondria, leading to AMP-activated protein kinase activation and subsequent increased glucose uptake by the cells, as measured in the mouse C2C12 muscle cell line. Based on the inhibition of NADH dehydrogenase (IC50 27µmolL −1 ), one of these compounds is close to a thousand fold more potent than metformin. There are no indications of off target effects. The compounds have the potential to have a greater anti-diabetic effect at a lower dose than metformin and may represent a new anti-diabetic compound class. The mechanism of action appears not to be as an insulin sensitizer but rather as an insulin substitute.